1937
DOI: 10.1084/jem.65.3.393
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Weight of Antibodies

Abstract: 1. Highly purified rabbit Type III pneumococcus anticarbohydrate proved to be homogeneous in the ultracentrifuge and its sedimentation constant, 7.0·10–13, did not differ from that of the principal component of normal rabbit globulin or of immune rabbit globulin containing up to 50 per cent of anti-egg albumin. The molecular weight of antibody in the rabbit is therefore probably very close to that of the principal normal globulin component, namely, 150,000. 2. Highly purified horse Type I pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
2

Year Published

1937
1937
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(42 citation statements)
references
References 9 publications
3
37
0
2
Order By: Relevance
“…Thus the sedimentation constant of S = 19 corresponds to the component with a molecular weight of about 990,000, whereas the lower sedimentation constant of S = 8.7 may be identified as the component with a molecular weight of about 170,000. It is of interest to note that upon dilution the relative amount of the heavy component increases, as was previously noted by Heidelberger and Pedersen (28).…”
Section: Resultssupporting
confidence: 59%
“…Thus the sedimentation constant of S = 19 corresponds to the component with a molecular weight of about 990,000, whereas the lower sedimentation constant of S = 8.7 may be identified as the component with a molecular weight of about 170,000. It is of interest to note that upon dilution the relative amount of the heavy component increases, as was previously noted by Heidelberger and Pedersen (28).…”
Section: Resultssupporting
confidence: 59%
“…Since data are available on the molecular weights of thyroglobulin (3) and at least a limited number of antibodies formed in the rabbit (20) it is possible to calculate the empirical composition of the specific precipitate at certain limiting points or regions of the reaction range. In the region of extreme antibody excess, as in the serial experiments (Table VI) ratios of antibody N to Tg N (or antibody to Tg) as high as 12.9 were encountered.…”
Section: Discussionmentioning
confidence: 99%
“…The Action of Horse Serum upon the Pulmonary Lesion.-The antibody contained in antipneumococcal horse serum is known to be of larger molecular size than the corresponding rabbit antibody (25,26). It has been suggested that the antibody of rabbit serum may be able to penetrate tissues more readily (27) and may, therefore, be more effective as a therapeutic agent.…”
Section: Zone Of Early Consolidation Andmentioning
confidence: 99%